USING HOMOGENIZATION AND NANOINDENTATION FOR MICROFIBRIL ANGLE DETERMINATION OF SPRUCE - Lucie Kucíková; Vladimír Hrbek; Jan Vorel; Michal Šejnoha (Acta Polytechnica CTU Proceedings)
This paper is concerned with the evaluation of microfibril angle of spruce. The microfibril angle is defined as an inclination of microfibrils from the longitudinal axis, the direction of lumens. It is well known and further supported by the present study that the microfibril angle has a great influence on the final mechanical properties of wood. This angle could be measured either directly using, e.g. polarisation microscopy, X-ray diffraction, infrared spectroscopy, or indirectly, as used in this study, by employing the nanoindentation measurements. Therein, the measured indentation modulus is compared with that obtained numerically using the anisotropic theory of indentation. The latter one depends on the entire stiffness matrix derived through homogenization and the searched microfibril angle. In view of the cell wall microstructure, the effective cell properties were found using the two-step micromechanical homogenization adopting both the Self-consistent and Mori-Tanaka methods.